Kenneth Whitehead: capstone - Whitehead, Kenneth, artist (Colorado State University. Libraries, 2025)
The artist's statement: Hello! My name is Kenneth Whitehead, I'm a graphic designer with a passion for blending playfulness with purpose. My work is all about creating designs that are both engaging and clear visuals that catch your eye and make you think. I love to play with color, typography, and shape, finding ways to balance boldness with simplicity. Each project is an opportunity to explore new ideas and create something that feels fresh but still functional. Over the years, I've had the chance to work on a variety of projects, from designing logos for Airbnb listings to crafting posters for events and personal initiatives. In each case, my goal is to create designs that not only look good but also serve a clear purpose. Whether it's a logo that represents a brand's identity or a poster that communicates an event's vibe, I want my work to resonate with the audience in a meaningful way. My process starts with simple sketches or brainstorming sessions where I let ideas flowerily primarily find inspiration from many cartoons and pop culture references that are appealing to a large group of people. I also find inspiration in the world around me whether it's in the shapes, colors, or patterns I encounter daily. From there, I refine my designs, experimenting with different styles and making sure that every element works together to communicate the message. I'm always looking for ways to add a touch of personality or unexpected detail to my work without losing sight of the core idea. I work with a mix of traditional tools like pencil and paper, as well as digital tools like Adobe Illustrator and Photoshop, depending on what the project calls for. I believe in the power of collaboration, so I enjoy working with clients to bring their vision to life. From the first concept to the final product, I make sure we're on the same page and that the design reflects their goals while adding something unique. Ultimately, my aim is to create designs that feel approachable and effective, something that catches your eye, tells a story, and sticks with you long after you've seen it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design